Spin polarization of carriers in InGaAs self-assembled quantum rings inserted in GaAs-AlGaAs resonant tunneling devices - Gordo, V. Orsi; Gobato, Y.G.; Galeti, H.V.A.; Brasil, M.J.S.P.; Taylor, David; Henini, M. (Springer, 2017)
In this work, we have investigated transport and polarization resolved photoluminescence (PL) of n-type GaAs-AlGaAs resonant tunneling diodes (RTDs) containing a layer of InGaAs self-assembled quantum rings (QRs) in the quantum well (QW). All measurements were performed under applied voltage, magnetic fields up to 15 T and using linearly polarized laser excitation. It was observed that the QRs’ PL intensity and the circular polarization degree (CPD) oscillate periodically with applied voltage under high magnetic fields at 2 K. Our results demonstrate an effective voltage control of the optical and spin properties of InGaAs QRs inserted into RTDs.